Kv7(KCNQ)-K+-Channels Influence Total Peripheral Resistance in Female but Not Male Rats, and Hamper Catecholamine Release in Hypertensive Rats of Both Sexes - Berg, Torill (Frontiers in Physiology, 2018)
K+-channels of the Kv7/KCNQ-family hyperpolarize and stabilize excitable cells such as autonomic neurons and vascular smooth muscle cells (VSMC). Kv7 may therefore play a role in blood pressure (BP) homeostasis, and prevent a high total peripheral vascular resistance (TPR), a hallmark of hypertensive disease. The present study analyzed if Kv7 channels influence catecholamine release and TPR in normotensive (WKY) and spontaneously hypertensive rats (SHR), and if they may contribute to the antihypertensive protection seen in young, female SHR. Tyramine-stimulated norepinephrine release evokes an adrenergic cardiovascular response, and also allows modulation of release to be reflected in the overflow to plasma. The experiment itself activated some secretion of epinephrine. The results show: 1) XE-991 (Kv7.1-7.4-inhibitor), but not chromanol 293B (Kv7.1-inhibitor), increased tyramine-stimulated norepinephrine overflow and epinephrine secretion in both sexes in SHR, but not WKY. 2) Surprisingly, the Kv7-openers retigabine (Kv7.2-7.5) and ICA-27243 (Kv7.2-7.3-preferring) increased catecholamine release in female SHR. 3) The rise in TPR following tyramine-stimulated norepinephrine release was increased by XE-991 but not chromanol in the female WKY only. 4) Retigabine and ICA-27243 reduced the TPR-response to tyramine in the female SHR only. These results suggested: 1) Up-regulation of Kv7.2-7.3 function in sympathetic neurons and chromaffin cells hampered catecholamine release in SHR of both sexes. 2) The increase catecholamine release observed after channel openers in the female SHR may possibly involve reduced transmission in cholinergic neurons which hamper catecholamine release. These two mechanisms may serve to counter-act the hyperadrenergic state in SHR. 3) Kv7.4, most likely in the vasculature, opposed the tension-response to norepinephrine in the female WKY. 4) Vascular Kv7.4-7.5 could be stimulated and then opposed norepinephrine-induced vasoconstriction in the female SHR. 5) Vascular Kv7 channels did not counter-act norepinephrine induced vasoconstriction in male rats, possibly due to different Kv7 channel regulation. Kv7 channels may represent a novel target for antihypertensive therapy.